The Effect Of Providing The Chin Tuck Method With A Working Posture Correction On The Fhp Conditions - Romadhoni, Dea Linia; Ramadhani , Alinda Nur (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: Musculoskeletal Disorders (MSDs) are a form of complaint that occurs in muscles, bones, joints, ligaments and tendons. Globally, musculoskeletal disorders are the single largest cause of work-related health complaints with more than 33% of all newly reported illnesses. Risk factors that contribute to causing MSDs are social factors. This study aims to analyze the effect of providing the chin touch method with working posture correction on forward head posture conditions. Methods: This type of research is analytical observational with a cross-sectional method. The research subjects were 32 respondents. This research is quantitative research with an experimental research design with a One Group Pretest and Posttest Design research design. Conducted in April-August 2023. Results: The results of analysis using the Wilcoxon test showed that there was a significant effect (p <0.046) by providing posture correction with the addition of Chin Tuck on reducing the degree of Forward head posture. Conclusion: The provision of working posture correction combined with the Chin Tuck method significantly reduces the degree of Forward Head Posture in respondents. This intervention can be an effective approach to addressing musculoskeletal complaints related to poor posture.